The usage of online databases in academic library: a case study of Perpustakaan Sultan Badlishah (PSB) / Nor Syafikah Nor Shaimi - Nor Shaimi, Nor Syafikah (2013)
Online databases are one of the major achievements of this process. Within a short period, they have become a key source of recent and reliable ieformation for a range of users in all scientific areas. Therefore, a study on the usage of online database in academic library has been conducted. A well structured questionnaire was designed to collect data, while a four point Likert Scale from 1 (Strongly disagree) to 4 (Strongly agree) was used to measured the usage of online databases am0ng respondent. The objectives of this research is to investigate frequency of usage, the effectiveness of online databases toward students and the problem faced by the students when using online database . The findings of the result shown the usage of online database in Perpustakaan Sultan Badlishah are still minimum.